Scientific integration for social and environmental strengthening. - José Crisólogo de Sales Silva (Diversitas Journal)
Scientific integration is essential for advancing knowledge and solving complex problems that affect both society and the environment.  Interdisciplinary collaboration allows for a more holistic approach to challenges, uniting different areas of knowledge to develop innovative solutions. Science, when integrated with social and environmental sectors, can promote more effective and sustainable public policies.